2021
DOI: 10.1128/mbio.02939-21
|View full text |Cite
|
Sign up to set email alerts
|

mDia1 Assembles a Linear F-Actin Coat at Membrane Invaginations To Drive Listeria monocytogenes Cell-to-Cell Spreading

Abstract: Listeria monocytogenes spreads from one cell to another to colonize tissues. This cell-to-cell movement requires the propulsive force of an actin-rich comet tail behind the advancing bacterium, which ultimately distends the host plasma membrane into a slender bacterium-containing membrane protrusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 84 publications
(127 reference statements)
0
6
0
Order By: Relevance
“…While these proteins have been examined at intercellular spreading events, their localizations at S. flexneri membrane protrusions and/or membrane invaginations are not easily ascertainable. Fortunately, as shown above, our mixed-cell assays (Dhanda et al, 2019;Dhanda et al, 2020;Dhanda, Vogl, Ness, et al, 2021;Dhanda, Yang, Kooner, & Guttman, 2021) provide a way to clearly visualize these proteins at the precise sites of cell-to-cell spreading. Furthermore, many of these factors remain unexplored at S. flexneri comet/rocket tails.…”
Section: Examination Of Host Clathrin Proteins and Endocytic Lipid Sp...mentioning
confidence: 89%
See 3 more Smart Citations
“…While these proteins have been examined at intercellular spreading events, their localizations at S. flexneri membrane protrusions and/or membrane invaginations are not easily ascertainable. Fortunately, as shown above, our mixed-cell assays (Dhanda et al, 2019;Dhanda et al, 2020;Dhanda, Vogl, Ness, et al, 2021;Dhanda, Yang, Kooner, & Guttman, 2021) provide a way to clearly visualize these proteins at the precise sites of cell-to-cell spreading. Furthermore, many of these factors remain unexplored at S. flexneri comet/rocket tails.…”
Section: Examination Of Host Clathrin Proteins and Endocytic Lipid Sp...mentioning
confidence: 89%
“…Evidence for this comes from studies showing that the actin polymerization necessary for L. monocytogenes initial invasion and enteropathogenic Escherichia coli (EPEC) pedestal formation follows (and requires) clathrin (Veiga et al, 2007). Conversely, we recently showed that caveolin accumulation around L. monocytogenes membrane invaginations requires (and follows) mDia1-mediated actin polymerization at the structures (Dhanda, Vogl, Ness, et al, 2021). However, whether or not F-actin accumulates around S. flexneri membrane invaginations prior to caveolin/clathrin or is a consequence of their presence remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This mode of elongation imposes frequent interactions between FH1 and the barbed end, which would likely reduce the probability of formins to lag behind the barbed end. In addition, active formins are thought to be anchored to membranes 28 , which should restrict further their ability to diffuse along the core of actin filaments.…”
Section: Discussionmentioning
confidence: 99%